2005
DOI: 10.1182/blood-2004-08-3367
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Polycomb M33 is required for splenic vascular and adrenal gland formation through regulating Ad4BP/SF1 expression

Abstract: Mice with disrupted mammalian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 56 publications
8
50
0
Order By: Relevance
“…This is the case for genetic ablation of factors such as Sf-1 (Luo et al, 1994), Pbx1 (Schnabel et al, 2003), M33 (Cbx2 -Mouse Genome Informatics) (Katoh-Fukui et al, 2005) and Odd1 (Osr1 -Mouse Genome Informatics) (Wang et al, 2005). Although these observations conform to the idea of a common developmental origin of these two tissues, these models do not provide insight into the developmental and molecular mechanisms that underlie the specification of one or other primordium from the AGP.…”
Section: Introductionmentioning
confidence: 43%
“…This is the case for genetic ablation of factors such as Sf-1 (Luo et al, 1994), Pbx1 (Schnabel et al, 2003), M33 (Cbx2 -Mouse Genome Informatics) (Katoh-Fukui et al, 2005) and Odd1 (Osr1 -Mouse Genome Informatics) (Wang et al, 2005). Although these observations conform to the idea of a common developmental origin of these two tissues, these models do not provide insight into the developmental and molecular mechanisms that underlie the specification of one or other primordium from the AGP.…”
Section: Introductionmentioning
confidence: 43%
“…M33 deficient mice have partial male-to-female sex reversal and smaller adrenals [62,63]. Consistent with these phenotypes, gonad development is markedly impaired at E11.5 and expression of Sf-1 is reduced to 50% of wild-type levels in the E16.5 adrenals.…”
Section: M33supporting
confidence: 49%
“…Indeed, ChIP assays showed that M33 binds to Sf-1 upstream regulatory regions in mouse Y1 adrenocortical cells. These regions did not overlap with the 674bp AGP promoter or with the FAdE [63]. The role of M33 in the control of Sf-1 expression in the AGP or the adrenal primordium thus remains unclear, although it could be implicated in the formation of intergenic boundaries impinging upon expression of the whole locus.…”
Section: M33mentioning
confidence: 99%
“…It has been shown that disruption of SF-1 also causes developmental abnormalities in spleen tubular structure and impaired clearance by the splenic vascular system . Similar defects have been observed in mice with disruption of the mouse polycomb 33 gene (M33) and suggest an interaction between M33 and SF-1 in splenic development (Katoh-Fukui et al, 2005).…”
Section: Role In Anterior Pituitary Vmh and Spleenmentioning
confidence: 53%